Djetinjstvo u Agramu M. Krleže i pitanje osjetilne percepcije - Benčić, Živa (Array, 2003)
The narrative level of Krleža's Djetinjstvo u Agramu (Childhood in Agram), is based, due to the author's wish to convey his perceptive experience, on the strategy of recalling sensory data, a stream of "pictures" and impressions which defy conceptual interpretation. Sensory perception is emphasized as the most important and the only element of cognition. Krleža solves the dispute on the epistemological value of sensory perception similarly as his literary model St. Augustine, for whom a human soul without senses would be deprived of not only images created by immediate observation, but also of those stored in memory. But this is where the analogy ends. Augustine concentrates on the trans-worldly, which makes possible a higher interpretative level of sensory experience, while Krleža concentrates on sensory-pictorial memory, trying to free himself from intellectual memory, towards this-worldly, which keeps him in the domain of the authentic and real, but also the fragmentary. The fact that the author is condemned to transform his own sensory experience into symbols puts Krleža into a paradoxical position because he has to replace the real with the symbolic, and the sensory with intellectual. However, in the process of reading his works, the language does not separate us from a multitude of perceptive sensations.